Analisis Neraca Bahan Makanan Kabupaten Garut Tahun 2022 - Renaldi, Eddy; Pardian, Pandi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Regional governments evaluate regional food production conditions and availability over a certain period using food balance of materials (NBM) analysis using data from relevant agencies. An instrument for ensuring food supply in the region is important, so the research aims to look at the balance of food ingredients in the Garut Regency in 2022. The research was carried out deliberately and analyzed using the balance of the total food supply principle. The results of the research show that food ingredients capable of meeting the consumption needs of the people of Garut Regency in 2022 are Rice, Corn, Wheat Flour, Starchy Foods, Oily Seeds, Fruits, Vegetables, Meat, Milk, Fish, Oils, Fats while ingredients Food that is not sufficient to meet the needs of the people of Garut Regency in 2022 is sugar and eggs.